Hydrolysis Process Optimization and Functional Characterization of Yak Skin Gelatin Hydrolysates. (13th October 2019) - Yang, Hui; Xue, Yanting; Liu, Jiaheng; Song, Shunyi; Zhang, Lei; Song, Qianqian; Tian, Li; He, Xiangyu; He, Shan; Zhu, Hongji
Abstract : Yak ( Bos grunniens ) is an animal mainly living on the Tibetan Plateau. Yak skin is a valuable resource that is wasted in the meat production process. This study aimed to prepare yak skin gelatin hydrolysates (YSGH) from yak skin through enzymatic hydrolysis and investigate functional characterization of YSGH. We showed that trypsin was more effective than neutrase, papain, and pepsin in increasing the degree of hydrolysis (DH) of YSGH. The conditions of enzymatic hydrolysis were optimized using central composite design (CCD) and response surface method (RSM), and the highest DH value of 31.96% was obtained. We then analyzed the amino acid compositions and molecular weight distribution of peptides in YSGH. The obtained YSGH exhibited certain antioxidant activity and excellent ACE-inhibitory activity (IC50 = 0.991 mg/mL). In addition, the solubility (98.79%), emulsification, and foaming properties of YSGH developed here were also evaluated. With these physicochemical and biological functions, YSGH had potential applications in food, pharmaceuticals, and cosmetics as an ingredient.